The Disaggregation of within-person and between-person effects in longitudinal models of change. [article]. - Curran, Patrick J.
Longitudinal models are becoming increasingly prevalent in the behavioral sciences, with key advantages including increase power, more comprehensive measurement, and establishment of temporal precedence. This review explores both substantive and quantitative issues related to the disaggregation of effects overtime, with a particular emphasis placed on the multilevel model. Existing analytic methods are reviewed, a general approach to the problem is proposed, and both the existing and proposed methods are demonstrated ujsing several aritifical data sets. Potential limitations and directions for future research are disucssed, and recommendations for the disagrregation of effects in practice are offered. - (from the authors)
Keywords: Bauer, Daniel J; Multilevel modeling; Growth modeling; Trajectory analysis; Within-person effects